Formulasi dan Uji Aktivitas Antibakteri Streptococcus mutans Pada Sediaan Obat Kumur Kombinasi Ekstrak Daun Seledri (Apium graveolens) dan Daun Jambu Biji (Psidium guajava) - Yardha, Muahamad; Halimatushadyah, Ernie; Yuliana, Agnes (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Dental caries is a disease of hard tissue caused by the activity of acid-producing bacteria that ferment carbohydrates after human consumption caused by the bacteria Streptococcus mutans. The flavonoid content in celery leaves and the tannin content in guava leaves can be used as an antibacterial treatment. Pharmaceutical preparations that can be used to treat dental caries problems are mouthwash. This research aims to formulate a combination of celery leaf and guava leaf extracts into a mouthwash preparation as an antibacterial against Streptococcus mutans. The research method used was experimental by testing the antibacterial activity of Streptococcus mutans in vitro. The results of the study showed that (1) the results of the antibacterial activity test on the negative control mouthwash were that the mouthwash base had no inhibition zone (2) the positive control chlorhexidine had an inhibition zone of 14.27mm (3) with a comparison between celery leaf extract and guava leaf extract 1:3 seeds, the results obtained were that the diameter of the inhibition zone at 20% concentration was 10.20 mm, 40% concentration was 11.20 mm, and 60% concentration was 12.05 mm; (4) The inhibitory power against Streptococcus mutans bacteria of the mouthwash containing a combination of celery leaf extract and guava leaf extract is greater than the inhibitory power of the positive control.